The God Hypothesis: Discovering Design in Our Just Right Goldilocks Universe - Corey, Michael A. (Rowman & Littlefield Publishers, 2001)
Seeks to reverse these profound misunderstandings by showing how the latest scientific evidence points in precisely the opposite direction.